2017
DOI: 10.1016/j.jplph.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

PtAUREO1a and PtAUREO1b knockout mutants of the diatom Phaeodactylum tricornutum are blocked in photoacclimation to blue light

Abstract: Aureochromes are blue light receptors specifically found in photosynthetic Stramenopiles (algae). Four different Aureochromes have been identified in the marine diatom Phaeodactylum tricornutum (PtAUREO 1a, 1b, 1c, and 2). Since blue light is necessary for high light acclimation in diatoms, it has been hypothesized that Aureochromes might play an important role in the light acclimation capacity of diatoms. This hypothesis was supported by an RNAi knockdown line of PtAUREO1a, which showed a phenotype different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Another study has shown the positive impact of supplementing different light colors on Chlamydomonas reinhardtii culture [13]. Through various studies, it was suggested that different classes of photoreceptors have specific responses to specific light mediated by different light-signaling pathways that are yet to be completely elucidated [2,37,38]. The other physiological phenomenon that can change the culture conditions is the rate of photoinhibition, which seems to be higher in W as compared to R. The energy of each photon is inversely proportional to the wavelength.…”
Section: Growth Curve Analysis Of P Tricornutum During Red Light Shiftmentioning
confidence: 99%
“…Another study has shown the positive impact of supplementing different light colors on Chlamydomonas reinhardtii culture [13]. Through various studies, it was suggested that different classes of photoreceptors have specific responses to specific light mediated by different light-signaling pathways that are yet to be completely elucidated [2,37,38]. The other physiological phenomenon that can change the culture conditions is the rate of photoinhibition, which seems to be higher in W as compared to R. The energy of each photon is inversely proportional to the wavelength.…”
Section: Growth Curve Analysis Of P Tricornutum During Red Light Shiftmentioning
confidence: 99%
“…Since in AUREO1a-silenced strains remnant AUREO1a protein could be present, or might be functionally replaced by one of the other aureochromes, AUREO1a and AUREO1b knock-out mutants of P. tricornutum have been generated by genome editing via TALEN technology (Serif et al, 2017). The results of this study has been published by Mann et al (2017), showing for the first time that AUREO1a-deficient mutants are strongly impaired in acclimation to high BL, as documented by a strong reduction in both photosynthetic and NPQ capacity. In contrast, in RL the differences between the AUREO1a deficient mutant and the wild type cells is smaller, but significant.…”
Section: Phenotypes Of Aureochrome1a and Aureochrome1b Knock-out Mutamentioning
confidence: 99%
“…Yeast two-hybrid screening has demonstrated a strong interaction between SjAUREO and the 40S ribosomal protein S6, which might be involved in blue light-mediated cellular division and photomorphogenesis [10]. In the single cellular diatom Phaeodactylum tricornutum, PtAUREO1a and PtAUREO1b mutants exhibit signi cantly decreased photoacclimation to blue light [11,12]. AUREO1 in Heterosigma akashiwois may act as a blue light-sensitive negative gene regulator, which is driven by dark-to-light transitional cues [13].…”
Section: Introductionmentioning
confidence: 99%